2020
DOI: 10.1111/trf.15672
|View full text |Cite
|
Sign up to set email alerts
|

ABO‐incompatible kidney transplantation can be successfully conducted by monitoring IgM isoagglutinin titers during desensitization

Abstract: BACKGROUND Recent advances in desensitization techniques and immunosuppressive therapy have led to improved outcomes after ABO‐incompatible (ABO‐i) kidney transplantation (KT). However, questions remain unanswered, particularly regarding which type of ABO isoagglutinin—immunoglobulin M (IgM) or immunoglobulin M (IgG)—is significantly involved in antibody‐mediated rejection (AMR). STUDY DESIGN AND METHODS We retrospectively analyzed data from 120 patients who underwent ABO‐i KT between 2012 and 2014. Preoperati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 42 publications
2
13
0
Order By: Relevance
“…The clinical efficacy of incompatible FFP use based on reduction in the isoagglutinin titer was within our expectations; target isoagglutinin titers were achieved in all cases. The rate of reduction in the isoagglutinin titer was comparable to a previously reported range using AB plasma (1‐3 titers vs 1.55‐1.66 per session) 10 . Regarding the removal of anti‐HLA antibodies, incompatible FFP exhibited reduction rates (25.3%‐35.3% per session) similar to those mentioned in a previous report 14 .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The clinical efficacy of incompatible FFP use based on reduction in the isoagglutinin titer was within our expectations; target isoagglutinin titers were achieved in all cases. The rate of reduction in the isoagglutinin titer was comparable to a previously reported range using AB plasma (1‐3 titers vs 1.55‐1.66 per session) 10 . Regarding the removal of anti‐HLA antibodies, incompatible FFP exhibited reduction rates (25.3%‐35.3% per session) similar to those mentioned in a previous report 14 .…”
Section: Discussionsupporting
confidence: 87%
“…Test sera were incubated at ambient temperature with either 3% Affirmagen A1 or B cells (Ortho Clinical Diagnostics, Raritan, The United States). The dilution in the last tube with an agglutination score of greater than 1+ was interpreted as the IgM isoagglutinin titer, while the IgG titer was determined by the addition of 0.1 mL polyspecific AHG (Millipore, Livingston, The United Kingdom) to each test tube 10,11 . HLA crossmatching (complement dependent cytotoxicity crossmatch and flow cytometry crossmatch) was performed using isolated lymphocytes.…”
Section: Methodsmentioning
confidence: 99%
“…The correlation of IgG with a low graft survival rate and AMR was reported 23 . However, Kim et al 24 revealed no difference in prognosis between an IgG titer of ≥16 and ≤8 when the pretransplant IgM titer was decreased to ≤4. Accordingly, the authors confirmed that ABO‐ILKT can be conducted by monitoring the IgM anti‐A/B titer during desensitization.…”
Section: Current Proceduresmentioning
confidence: 96%
“…It has been reported that the IgM antibody is involved in ABO-incompatible transplantation, and desensitization therapy using the IgM-type ABO antibody titer as an index is useful for preventing AMR development [127]. Contrarily, other reports stated that IgG-type ABO antibodies are risk factors for the development of AMR [128].…”
Section: The Role Of Igm Antibodies In Abo-incompatible Transplant Sumentioning
confidence: 99%